IMPLEMENTASI MANAJEMEN KELAS BERBASIS KEDISIPLINAN UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Mirzontoni Mirzontoni Mirzontoni (UNIVERSITAS BENGKULU, 2016)
The objective of the research was to improve the student’s motivation by using a technique of dicipline-based classroom management. The design used was an action researchimplemented four stages: plan, implementation, observation, and reflection. The subjects of this research were the students of XI Basic Science Class Senior High School 1 Muara Pinang. The data collection techniques used were observation, interview, and documentation. The result of this research show that: to managemen class based on discipline cam to improved the motivation student in atten, to motivation join in learning. And it cam to the student improved motivation student in doing the exarciss and tol son improve the motivationstudent in study.Keywords: classroom management, disiplne, motivation